Effect of nutritional factors and precursors on formation of colchicine in Gloriosa superba in vitro - Pandurangan, Bharathi; Philomina, D. (Research in Biotechnology, 2010)
In the present work we investigated the effect of nutritional factors and the precursors on colchicine production in callus cultures of Gloriosa superba in order to optimize the colchicine production in vitro. To broaden the significance of our study, we have investigated the effect of plant growth regulators, carbon, nitrogen and inorganic ions such as sodium sulphate, calcium chloride, potassium hydrogen phosphate and ferric sulphate at different concentration and analyzed colchichine content using petroleum ether and dichloromethane extraction and HPLC. Colchicine content in the callus, grown in the medium with sucrose as carbon source and 40 mM ammonium nitrate as nitrate source showed the greatest promise with highest biomass and colchicine content. In addition to this, sulphate ions (40 mM) markedly increased the formation of colchicine. In contrast, highest concentration of phosphate (2.5 mM) and calcium (10 mM) were found to be inhibitory for colchicine formation. Precursors (40 ÃŽÂ¼M tyrosine) also influenced the colchicine content (9.79 mM dry weight) with the above mentioned nutritional effect. The results presented here highlight the optimum condition for the colchicine production in Gloriosa superba.